Minat Melanjutkan Studi Ke Perguruan Tinggi Ditinjau Dari Prestasi Belajar Kejuruan Akuntansi Dan Profesi Orang Tua Pada Siswa Kelas XI Program Keahlian Akuntansi SMK Negeri 1 Sukoharjo Tahun Ajaran 2015/2016 - Kurniawan, Abdul Hanif; , Dr. Sabar Narimo, M.M., M.Pd; , Dra.Titik Asmawati, S.E, M.Si (2016)
The purpose of this study was to determine: 1) the influence of the learning achievement of vocational accounting on the interest to continue their studies to university, 2) the influence of the profession of parents against the interest of continued study higher education, 3) the influence between the learning achievement of vocational accounting and profession of parents of interest continue their studies to university. This research is a quantitative descriptive research whose conclusions obtained based on the results of statistical analysis. The population in this study were all students of class XI Accounting Expertise Program SMK Negeri 1 Sukoharjo the academic year 2015/2016 with a sample of 84 students using simple random sampling technique. methods of data collection using documentation and questionnaires. Questionnaire first be tested to determine the level of validity and reliability. Test requirements analysis in the form of normality and linearity test, to engineering data analysis using multiple linear regression analysis, t test, F test, the coefficient of determination as well as the effective contribution and relative contribution. Results of regression analysis regression equation: Y = 13.134 + 3.081 X1 + 0.751 X2 + e, which means that interest to continue their studies to university is by learning achievement and vocational accounting profession parents. Based on the analysis and discussion can be concluded that: (1) the achievement of vocational learning accountancy positive effect on the interest to continue their studies to university. It is evident from the regression analysis obtained by value t count> t table is 2,272> 1,989 with significant value 0.026 <0.05. (2) the profession of parents has positive influence on the interest to continue their studies to university. It is evident from the regression analysis obtained by value t count> t table is 3,154> 1,989 with significant value 0.002 <0.05. (3) vocational learning achievement and the accounting profession parents jointly positive effect on the interest to continue their studies to university. It is evident from the regression analysis obtained F count> F table is 9.040> 3.11 with significant value 0.000 <0.05. (4) vocational learning achievement variable accounting provides effective contribution of 6.62%. Variable profession gives parents the effective contribution of 11.58%, with a coefficient of determination (R2) of 0.182, or 18.2%, while 81.8% are influenced by other variables not examined.. Keywords: Learning Achievement Vocational Accounting Profession Parents' Interests to the College of Continuing Studies